Plant characterization of genetically modified maize hybrids MON-89Ø34-3 × MON-88Ø17-3, MON-89Ø34-3 × MON-ØØ6Ø3-6, and MON-ØØ6Ø3-6: alternatives for maize production in Mexico - Heredia Díaz, Oscar; Aldaba Meza, José Luis; Baltazar, Baltazar M.; Bojórquez Bojórquez, Germán; Castro Espinoza, Luciano; Corrales Madrid, José Luis; De la Fuente Martínez, Juan Manuel; Durán Pompa, Héctor Abel; Alonso Escobedo, José; Espinoza Banda, Armando; Garzón Tiznado, José Antonio; González García, Juvencio; et al. (2016)
Abstract Environmental risk assessment (ERA) of genetically modiﬁed (GM) crops is a process to evaluate whether the biotechnology trait(s) in a GM crop may result in increased pest potential or harm to the environment. In this analysis, two GM insect-resistant (IR) herbicide-tolerant maize hybrids (MON-89Ø34-3 9 MON-88Ø17-3 and MON-89Ø34-3 9 MON-ØØ6Ø3-6) and one herbicide-tolerant GM hybrid (MON-ØØ6Ø3-6) were compared with conventional maize hybrids of similar genetic backgrounds. Two sets of studies, Experimental Phase and Pilot Phase, were conducted across ﬁve ecological regions (ecoregions) in Mexico during 2009–2013, and data were subject to meta-analysis. Results from the Experimental Phase studies, which were used for ERA, indicated that the three GM hybrids were not different from conventional maize for early stand count, days-tosilking, days-to-anthesis, root lodging, stalk lodging, or ﬁnal stand count. Statistically signiﬁcant differences were observed for seedling vigor, ear height, plant height, grain moisture, and grain yield, particularly in the IR hybrids; however, none of these phenotypic differences are expected to contribute to a biological or ecological change that would result in an increased pest potential or ecological risk when cultivating these GM hybrids. Overall, results from the Experimental Phase studies are consistent with those from other world regions, conﬁrming that there are no additional risks compared to conventional maize. Results from Pilot Phase studies indicated that, compared to conventional maize hybrids, no differences were detected for the agronomic and phenotypic characteristics measured on the three GM maize hybrids, with the exception of grain moisture and grain yield in the IR hybrids. Since MON-89Ø343 9 MON-88Ø17-3 and MON-89Ø34-3 9 MONØØ6Ø3-6 confer resistance to target insect pests, they are an alternative for farmers in Mexico to protect the crop from insect damage. Additionally, the herbicide tolerance conferred by all three GM hybrids enables more cost-effective weed management. Keywords Environmental risk assessment Center of origin of maize GM maize Meta-analysis Ecoregions Data transportability